2000
DOI: 10.1086/301586
|View full text |Cite
|
Sign up to set email alerts
|

A CCD Study of the Environment of Seyfert Galaxies. III. Host Galaxies and the Nearby Environments

Abstract: A technique is described that permits the robust decomposition of the bulge and disk components of a sample of Seyfert galaxies, as well as a (control) sample of non-active galaxies matched to the Seyferts in the distributions of redshift, luminosity and morphological classification. The structural parameters of the host galaxies in both samples are measured. No statistically significant differences at greater than the 95% level are found in these parameters according to a K-S test. "Companion galaxies" -defin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 22 publications
5
39
3
Order By: Relevance
“…In particular, it was suggested that interacting galaxies or galaxies with companions exhibit a significant excess of nuclear activity compared to isolated galaxies (Dahari 1984;Keel et al 1985;Rafanelli et al 1995). On the other hand, no relation was seen by other studies (Virani et al 2000;Schmitt 2001;Fuentes-Williams & Stocke 1988;MacKenty 1989;Laurikainen & Salo 1995). Hence the issue of possible relations between the environment and nuclear activity appears to be still controversial.…”
Section: Discussionmentioning
confidence: 92%
“…In particular, it was suggested that interacting galaxies or galaxies with companions exhibit a significant excess of nuclear activity compared to isolated galaxies (Dahari 1984;Keel et al 1985;Rafanelli et al 1995). On the other hand, no relation was seen by other studies (Virani et al 2000;Schmitt 2001;Fuentes-Williams & Stocke 1988;MacKenty 1989;Laurikainen & Salo 1995). Hence the issue of possible relations between the environment and nuclear activity appears to be still controversial.…”
Section: Discussionmentioning
confidence: 92%
“…Although past studies have sometimes produced ambiguous results, primarily because of the varying selection criteria of the AGN and control samples, such as morphology and luminosity, the general consensus appears to be that galaxies with active nuclei are more likely to be part of close pairs, possibly inducing nuclear activity through tidal perturbations. At low redshifts, the results have been mixed for Seyfert galaxies ( Dahari 1985;Fuentes-Williams & Stocke 1988;Virani et al 2000). On the other hand, more luminous quasars are usually found in small groups of galaxies, possibly increasing in richness at higher redshifts (e.g., Bahcall et al 1997 for QSOs at z < 0:3; Yee & Green 1987 for z % 0:6).…”
Section: The Local Environmentmentioning
confidence: 99%
“…Quasars Figure 1a displays the versus distribution of M BH L bulge 15 PG quasars (using and H 0 \ 80 km s~1 Mpc~1 ) 0 \ 1). The quasar sample is slightly revised from the L98 sample with the addition of PG 1425]267 from Kirhakos et al (1999) Virani et al (2000). The Spearman rank order correlation coefficient, its signiÐcance level, and the rms scatter are indicated above each panel.…”
Section: The Relationmentioning
confidence: 99%
“…M BH -M bulge The purpose of this paper is to better constrain the slope of the relation using recently published data. M BH -M bulge We use new determinations for 14 nearby galaxies M BH reported in G00 and new bulge luminosity, determi-L bulge , nations for nine Seyfert 1 galaxies by Virani, De Robertis, & VanDalfsen (2000), for which estimates can be M BH (Hb) made. In°2 we review the determination in M BH (Hb) quasars, the new in nearby galaxies, new in M BH L bulge Seyfert galaxies, and the resulting signiÐcantly nonlinear relation.…”
Section: Introductionmentioning
confidence: 99%